FIXATION PROCESS OF LAMINATED BAMBOO COMPRESSION FROM CURVED CROSS-SECTION SLATS - Darmawan, Teguh; Bahanawan, Adik; S. Adi, Danang; Dwianto, Wahyu; Nugroho, Naresworo (Indonesian Journal of Forestry Research, 2021)
Removing the outer part of bamboo for manufacturing flat bamboo lamination has disadvantage on the density of the product. The purpose of this experiment was to investigate the fixation of compressed bamboo from curved cross-section slats. The compression of bamboo slats using densification technique was aimed for uniform density. Furthermore, steam treatments were conducted to fix the deformation. The compressed bamboo slats revealed that the density of the samples at the bottom parts increased from 0.4–0.56 g/cm3 to 0.89–1.05 g/cm3 after pressing with a compression level between 46.98–63.97%, while the samples in the middle parts increased from 0.7–0.83 g/cm3 to 1.02–1.18 g/cm3 with the compression level of 32.92–41.5%. These results were slightly higher than that of the upper parts, which was between 0.91–0.98 g/cm3. The recovery of set decreased and the weight loss increased with increasing temperature and steam treatment time. Fixation of compressive deformation could be achieved at 160°C within 60 minutes. The bottom parts of samples experienced a slightly greater weight loss compared to the middle parts, i.e. 8.38% and 7.49%, respectively. The anatomical structure of bamboo tended to deform during densification process. Furthermore, the steam treatments affected the colour of densified bamboo which became darker. From this experiment, it can be concluded that the manufacture of laminated bamboo from bamboo slats can be uniformed in strength by equalizing the density at the bottom and middle with the upper parts through the densification technique.